HERITAGE IDENTITY CONSERVATION OF THE WOODCARVING PLACEMENT AND DESIGN COMPOSITION TYPOLOGIES ON JOHOR MALAY HOUSES - Yusof, Hanita; Ibrahim, Fawazul Khair; Raja Shahminan, Raja Nafida (PLANNING MALAYSIA, 2020)
Woodcarving is a distinct heritage that can promote the identity of a region. However, current practices of using the design composition and woodcarving placement which do not belong to the local region pose a threat to the identity and authenticity of the original heritage. If such practices continue and the identity of the local heritage is not preserved and recorded, the traditional designs and local identity will eventually be lost. The objective of this paper is to identify the placements of woodcarving and the typology of design compositions of woodcarving which form the identity of the Johor Malay houses. Site visits were conducted to Limas Johor in which the wood carvings of 50 houses were examined, photographed and documented. Interviews were also conducted with the house owners or occupants, and the wood carvers. The samples were analyzed and the results were verified by experts. A total of 10 woodcarving placements and 23 typologies were discovered, drawn and coded. The findings of this research suggest that the typology combination of JT2-P5+KT7 of woodcarving represents the identity of Limas Johor houses. It is hoped that this study can bring recognition to Johor woodcarvings, contribute valuable guides for woodcarvers to apply these typologies into their future works to sustain and cherish the Johor local identity.